Dorogoi Rezo - Dzhokhadze, Giuri (Russia : Marina Razbezhkina and Mikhail Ugarov School of Documentary Film and Documentary Theatre, 2015)
'Dear Rezo' is a comedic documentary about a Georgian in Moscow who can solve anyone's family problems, except his own. He is asked questions such as, how do I get expel my loneliness, should I return to my unfaithful husband and how do I make a man fall in love with me; answering them all whilst leaving himself unanswered.
Verzio Film Festival Submission
Keywords: Documentary films